Analisis Implementasi Model Triple Helix dalam Mendorong Inovasi Daerah - Akhlakul karimah; Ayu Suraya; Afrijal (Sociale : Journal of Social and Political Sciences, 2026)
The development of regional innovation in the knowledge-based economy highlights the importance of cross-sector collaboration as a key driver of regional competitiveness. This study examines the effectiveness of the Triple Helix model, which emphasizes the interaction between government, universities, and industry in fostering innovation at the regional level. The research aims to analyze how the synergy among these actors influences innovation performance and to identify key factors affecting its implementation. This study employs a qualitative descriptive approach using a library research method, relying on secondary data from recent scientific articles and relevant literature. Data were analyzed through content analysis to identify patterns, relationships, and critical issues within the Triple Helix framework. The findings indicate that the effectiveness of the Triple Helix model largely depends on the quality of collaboration, institutional support, and balance of roles among actors. Strong coordination, adequate funding, skilled human resources, and supportive infrastructure significantly enhance innovation outcomes. However, challenges such as weak policy integration, limited industry participation, and gaps between academic research and market needs hinder optimal implementation. Despite these constraints, opportunities arise from digital transformation and the development of innovation clusters that can strengthen collaboration and accelerate knowledge transfer. The study concludes that improving coordination mechanisms and fostering mutual trust among stakeholders are essential to enhance the effectiveness of the Triple Helix model in promoting sustainable regional innovation.